Blasting Impact Simulation Test and Fragmentation Distribution Characteristics in an Open-Pit Mine - Xiaohua Ding; Xiang Lu; Wei Zhou; Xuyang Shi; Boyu Luan; Ming Li (Shock and Vibration)
Based on the split Hopkinson pressure bar (SHPB) test system, dynamic impact tests of coal specimens under different impact pressures were carried out to study the relationship between the impact load and the size of crushed lump coal. Based on the theory of stress wave attenuation, the relationship between the blasting impact load in a single-hole blasting area of a coal seam and the load applied in an impact failure test of a coal specimen in the laboratory was established. According to the characteristics of the fragmentation distribution of the coal specimens destroyed under a laboratory impact load and the requirement of the minimum cost control of coal blasting in an open-pit coal mine, the fragmentation size range was divided into three groups: large-diameter, medium-diameter, and powder particles. Based on this range, the variation rule of the mass percentage of coal fragments with impact pressure was obtained. Established on the evaluation principle of the blasting effect in an open-pit coal mine, a good impact fragmentation effect was obtained. The good pressure range is 0.30 MPa≤P<0.90 MPa.